Analisis Faktor-Faktor dalam Perencanaan Alokasi Tenaga Kerja Konstruksi pada Proyek Rehabilitasi dan Rekonstruksi Sarana Pendidikan Universitas Tadulako Fase I - andi asnudin; Ibnu Rahmatullah (Universitas Bengkulu, 2024)
The purpose of this research was to find out what factors influenced the allocation of construction labor in the Phase II Tadulako University Educational Facilities Rehabilitation and Reconstruction Project. The type of research used in this research is quantitative research with a descriptive approach. The research method uses multiple linear regression analysis and data processing uses the Statistical Package for the Social Sciences version 26 application. This research uses 5 (five) variables, namely Cost (X1), Duration (X2), Volume (X3), Experience (X4) and Labor Allocation (Y). The number of samples or respondents in this research was 30 people who were management on the construction project. The partial research results show that all variables have a positive effect on craftsman performance with the regression equation Y = 2.309 + 0.51X1 + 0.519X2 + 0.168X3 + 0.480X4 but the only variables that have a significant effect are volume, duration and experience. Simultaneously, the variables cost, volume, duration and experience have a significant influence on labor allocation and it can be seen what factors have a significant influence on labor allocation.